Cadena logística integrada un apoyo al sector agrícola - Méndez Giraldo, Germán Andrés; Pinzón Catiblanco, Marco Antonio (Ingeniería, 2000)
The agricultural sector companies, have suffered the impacts of the global market and economical opening, it probably is the sector that more efforts should make by improving their levels of productivity prosecuting to increment their competitiveness. Efforts like the inclusion of the cluster, like integration logistics of the chains of transformation has shown their kindness. However, it should incorporate more and better technical for the managerial administration, this article pretends, not only, shows the more technical of administration, like they are the distribution requirements planning (DRP) and the material requirements planning (MRP), but rather, it base an opinion on the most robust technical of the classical operational research.